A systematic review and behaviour change technique analysis of remotely delivered alcohol and/or substance misuse interventions for adults. (1st October 2022) - Howlett, Neil; García-Iglesias, Jaime; Bontoft, Charis; Breslin, Gavin; Bartington, Suzanne; Freethy, Imogen; Huerga-Malillos, Monica; Jones, Julia; Lloyd, Nigel; Marshall, Tony; Williams, Stefanie; Wills, Wendy; et al.
Abstract: Background: There has been a lack of systematic exploration of remotely delivered intervention content and their effectiveness for behaviour change outcomes. This review provides a synthesis of the behaviour change techniques (BCT) contained in remotely delivered alcohol and/or substance misuse approaches and their association with intervention promise. Methods: Searches in MEDLINE, Scopus, PsycINFO (ProQuest), and the Cochrane Library, included studies reporting remote interventions focusing on alcohol and/or substance misuse among adults, with a primary behaviour change outcome (e.g., alcohol levels consumed). Assessment of risk of bias, study promise, and BCT coding was conducted. Synthesis focussed on the association of BCTs with intervention effectiveness using promise ratios. Results: Studies targeted alcohol misuse (52 studies) or substance misuse (10 studies), with predominantly randomised controlled trial designs and asynchronous digital approaches. For alcohol misuse studies, 16 were very promising, 17 were quite promising, and 13 were not promising. Of the 36 eligible BCTs, 28 showed potential promise, with seven of these only appearing in very or quite promising studies. Particularly promising BCTs were 'Avoidance/reducing exposure to cues for behaviour', 'Pros and cons' and 'Self-monitoring of behaviour'. For substance misuse studies, three were very promising and six were quite promising, with all 12 BCTs showing potential promise. Conclusions: This review showed remotely delivered alcohol and substance misuse interventions can be effective and highlighted a range of BCTs that showed promise for improving services. However, concerns with risk of bias and the potential of promise ratios to inflate effectiveness warrant caution in interpreting the evidence. Highlights: Remote approaches were mostly asynchronous digital approaches such as websites. Remote interventions targeting alcohol or substance misuse showed some promise. Reducing exposure to cues and listing pros and cons were promising techniques. More pre-registered protocols and process evaluation studies are needed.